Medial Hoffa Fracture: Description of a Novel Classification System and Rationale for Treatment Based on Fragment-Specific Fixation Strategy - Pires, Robinson Esteves; Bidolegui, Fernando; Pereira, Sebastián; Giordano, Vincenzo; Giordano, Marcos; Schröter, Steffen (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Purpose This study aims to present a novel classification system and a rationale for treatment of medial Hoffa fractures.Methods We developed a simple comprehensive classification system for medial Hoffa fractures based on the fragment size and presence of fracture comminution. Furthermore, we propose a treatment algorithm based on two pillars: our case series of nine patients presenting medial Hoffa fractures and the best evidence-based pertinent literature. Fracture healing, range of motion, function, and complications were evaluated after a minimum of 6 months follow-up.Results All fractures healed with no loss of reduction. Knee flexion ranged from 90 – 130° (mean 110°, standard deviation 15.2). Knee extension ranged from 0 – 10° (mean 1°, standard deviation 3.3). Knee function according to the Lysholm score ranged from 74 – 96 points (mean 85, standard deviation 6.3). There were no complications such as infection, fixation failure, or medial femoral condyle osteonecrosis. One patient required hardware removal due to soft tissue irritation and one patient underwent knee mobilization under anesthesia after 8 weeks of fracture fixation due to knee stiffness.Conclusion The presented rationale for treatment based on the new classification system is a simple and effective strategy on the decision-making process for adequate management of medial Hoffa fractures.
Keywords: Busch-Hoffa fractures; Hoffa fractures; distal femur fractures; coronal femur fractures; fracture fixation; open reduction; internal fixation